MOTIVATIONAL STRUCTURE AND ORIGIN OF BUSINESS NAMES - Iryna Oliinyk; Larysa Ruban; Liudmyla Schevchenko (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2018)
The paper deals with motivational structure of business names that determines the choice of strategy for naming. The article considers the origin of business names and concentrates on the fact that business names' formation requires the right combination of objective information and subjectivity. Business names of restaurants in Brussels are studied. The article analyses the requirements that business names should meet, presents the main components of their motivational structure and proposes a new classification of business names, taking into consideration their motivational and structural characteristics A new classification of business names  presented in the paper includes 8 different categories. The paper defines a correlation between the motivational structure of business names and the degree of persuasion they possess. The article demonstrates the use of different kinds of business names and their relevance for the naming process. It is shown that anthroponymic, transpositional and idiomatic business names possess the highest degree of persuasion. Toponymic, background and international business names can sometimes have a controversial effect on addressees, be irrelevant and highly questionable as potential actuators. The article concentrates on the necessity to adjust the code business names have to the needs of the target audience and shows the absence of direct correlation between transparency or vagueness of motivational characteristics and  low or high level of persuasion. The paper develops recommendations for the choice of effective linguistic means of expression in business names creation and proposes topics for further research in the field.